Climate change and loss, as if people mattered: values, places, and experiences. (13th June 2017) - Tschakert, Petra; Barnett, Jon; Ellis, Neville; Lawrence, Carmen; Tuana, Nancy; New, Mark; Elrick‐Barr, Carmen; Pandit, Ram; Pannell, David
Abstract : The United Nations Framework Convention on Climate Change (UNFCCC) is seeking to prepare for losses arising from climate change. This is an emerging issue that challenges climate science and policy to engage more deeply with values, places, and people's experiences. We first provide insight into the UNFCCC framing of loss and damage and current approaches to valuation. We then draw on the growing literature on value‐ and place‐based approaches to adaptation, including limits to adaptation, which examines loss as nuanced and sensitive to the nature of people's lives. Complementary perspectives from human geography, psychology, philosophy, economics, and ecology underscore the importance of understanding what matters to people and what they may likely consider to constitute loss. A significant body of knowledge illustrates that loss is often given meaning through lived, embodied, and place‐based experiences, and so is more felt than tangible. We end with insights into recent scholarship that addresses how people make trade‐offs between different value priorities. This emerging literature offers an opening in the academic debate to further advance a relational framing of loss in which trade‐offs between lived values are seen as dynamic elements in a prospective loss space. WIREs Clim Change 2017, 8:e476. doi: 10.1002/wcc.476 This article is categorized under: Climate, Nature, and Ethics > Comparative Environmental Values Abstract : When experiencing climate change impacts, people judge some of their lived values (what they value in their daily lives) more important than others and hence will try to protect those first or most, including through adaptation, to prevent intolerable loss, both in the present (a) and in the future (b).